All-Metal Slow-Wave-Structure of Coaxial-Radial Line Type for Powerful Multibeam TWT - Kasatkin, A. D.; Presnyakov, S. A.; Kravchenko, N. P.; Mukhin, S. V. (2019 Systems of Signal Synchronization, Generating and Processing in Telecommunications (SYNCHROINFO), 2019)
The subject of consideration of this work is the development of the design, algorithm and program for calculating the dispersion characteristics of the coaxial-radial line (CRL). The selected design of the CRL allows to optimize the coupling impedance and the dispersion of the SWS.